The Students’ Problem in Creative Writing Course - Tarisa Octavia (Indonesian Journal of English Language Studies (IJELS), 2025)
This study describes the students' problems in the creative writing course. Knowing these problems can help lecturers find out students' weaknesses in writing. Therefore, the researcher is interested in investigating the problems that exist when writing. The purpose of this research is to find out students' problems in writing in the Creative Writing Course. The researcher used quantitative descriptive methods. The population was taken from PGRI Wiranegara University English Language Education Study Program students’ classes 2020, 2021, and 2022, with a total of 89 students. Data collection through a questionnaire was carried out over 5 days using Google Forms from May 17th, 2024, to May 21st, 2022. Interviews were conducted on May 29th, 2024. Documentation was conducted on May 29th, 2024. There were 9 students interviewed, and they were chosen randomly. The researcher gave 15 questions through a questionnaire and gave 6 questions during interviews about students' writing problems. The results of this research show that students experience problems related to linguistic, cognitive, psychological, and pedagogical aspects. In this research, the dominant aspects are linguistic and cognitive. It is hoped that these findings can help students to minimize the difficulties they face, and lecturers can determine a suitable teaching style for students.